Speicherbedarf und dessen Auswirkungen auf die Energiewirtschaft bei Umsetzung der politischen Ziele zur Energiewende - Teufel, Felix (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2015)
Increasing integration of renewable energy sources is transforming the current powergeneration structure. This challenges policy makers, system operators, and also established energy system simulation tools. We developed a dynamic bottom-up model of the German electricity market to analyze the effects of high-resolution wind energy generation.